2002
DOI: 10.1590/s1413-78522002000400002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of tibial shaft fractures

Abstract: In this work an epidemiological analysis on tibial shaft fractures was performed. During four years, our service treated 179 fractures, 132 in male, 47 in female, aged 14 to 83 years. The 21 to 30-year-old patiens were the more injured. Of these, 120 were open and 59 close fractures of which prevailing cause was road traffic accident. The study based on patients promptuaries analyses and radiographs. The fractures occurred 97 times in the middle third (54.18%); 102 times (56.98%) presented simple fragments, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
(65 reference statements)
3
6
1
Order By: Relevance
“…In relation to gender, there was an agreement with other studies [8,9] in which males represented 79% of the cases. Such results are similar to several other studies [7,9,10] since males tend to show risky behavior, potentially causing accidents. This predominance of males tends to disappear with age, actually, there is a reversal of this predominance to females in old age [6].…”
Section: Resultssupporting
confidence: 92%
“…In relation to gender, there was an agreement with other studies [8,9] in which males represented 79% of the cases. Such results are similar to several other studies [7,9,10] since males tend to show risky behavior, potentially causing accidents. This predominance of males tends to disappear with age, actually, there is a reversal of this predominance to females in old age [6].…”
Section: Resultssupporting
confidence: 92%
“…Mechanism of injury: in our study, the main mechanism of injury was road traffic accident(64.9%), followed by fall from height (32.4%) and others (2.7 %), this is comparable with the epidemiological studies done by (C.M. Court-Brown et.al 1995) 6 and (Marco Aurelio Sertorio Grecco et al 2002) 7 . Side of fractures: our study shows that right side fractures more common in 42 patients 56.8%, while 32 patients 43.2% had left side fractures, and this is comparable with the study done by (Huang P et al 2008) 5 , (Marco Aurelio Sertorio Grecco et al 2002) 7 .…”
Section: Resultssupporting
confidence: 89%
“…Most of our patients have comminuted and oblique fracture in (81%), while transverse fracture found in (13.6%), spiral in (2.7%) and segmental in (2.7%). 6 and the study published by (Marco Aurelio Sertorio Grecco et al 2002) 7 . No significant differences were observed in our study between patients operated with intramedullary nail and those operated with plate & screw regarding age and gender (p>0.05), and our study shows that fracture shaft tibia is more common in young age males.…”
Section: Resultsmentioning
confidence: 83%
“…10 17 In our study close fractures were most commonly found. Among close fractures AO Type A2 taken the lead from others.…”
supporting
confidence: 55%